Optimizing the Role of School Administrators in Facing the Digital Era - Jahroo, Aanisah; Nuur’Ainii, Fitriyyah; Yaqien, Nurul; Triwiyanto, Teguh (Universitas Negeri Malang, 2024)
The development of information and communication technology in the digital era provides great opportunities for school administrators to improve the efficiency of data management and improve school administration services. This article uses a descriptive qualitative approach by referring to published articles and journals to find out more about how school administration personnel utilize existing technological developments, so as to optimize information management systems and maximize administrative processes in schools. With this approach, it can be seen that there are many opportunities for school administration personnel in terms of improving administrative services in an educational institution.